GlobAEROSOL: A 12 year global aerosol dataset from European satellite instruments - Thomas, G; Poulsen, C; Siddans, R; Sayer, A; Carboni, E; Navarro, Ó; Arjona, Ó; Grainger, R; Kerridge, B; Pinnock, S (2008)
GlobAEROSOL is an ESA Data User Element project to produce a global aerosol dataset from four separate European satellite radiometers: AATSR and MERIS, plus ATSR-2 (on board ERS-2) and SEVIRI (on the second generation Meteosats). Together these instruments provide a near continuous global dataset spanning 1995 -2007. Aerosol parameters (optical depth, Angstrom coefficient and aerosol type) are being produced in a consistent format from each individual instrument, as well as in 'merged aerosol products' that combine the results from multiple instruments. Details of the GlobAEROSOL product set are given and results from the on-going validation of these products are presented, as well as an overview of the analysis algorithms.